2020
DOI: 10.1088/1674-1056/abc15d
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network potential for gold clusters*

Abstract: In cluster science, it is challenging to identify the ground state structures (GSS) of gold (Au) clusters. Among different search approaches, first-principles method based on density functional theory (DFT) is the most reliable one with high precision. However, as the cluster size increases, it requires more expensive computational cost and becomes impracticable. In this paper, we have developed an artificial neural network (ANN) potential for Au clusters, which is trained to the DFT binding energies and force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…We choose radial basis function of G 2 type and angle basis function of G 4 type [37]. The details about ANN settings can be found elsewhere [28].…”
Section: Artificial Neural Network Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose radial basis function of G 2 type and angle basis function of G 4 type [37]. The details about ANN settings can be found elsewhere [28].…”
Section: Artificial Neural Network Potentialmentioning
confidence: 99%
“…Thorn et al benchmarked an ANN potential against a Gupta potential and an embedded atom model in the search of stable Au n clusters (30 n 80) to accelerate the ground-state structures (GSSs) search by firstprinciples [27]. Cao et al also developed ANN potential for Au 11-100 based on DFT data and test its accuracy by calculating energy and force of structures from previous reports [28]. As dedicated by the authors, ANN trained for a wide range of size is highly demanded by the applications, but now, its accuracy is coarse especially in the deal with competitive local energyminimum isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the emerging machine learning or deep learning (DL) techniques have provided a solution for rapid prediction of the energies of isomers for a molecule or cluster with precision comparable to DFT. For instance, using a geom-C60 database with four symmetric cage isomers and 29 unique C–C bonds, Aghajamali and Karton examined the performance of 12 carbon force fields and found that a machine-learning-based Gaussian approximation potential, namely, GAP-20, outperforms the empirical force fields. In addition to binding energies, Calvo et al created a large database of 753,184 infrared spectra of C n clusters ( n = 24, 33, 42, 52, 60) with different shapes (including fullerene-like cages, graphene-like flakes, pretzel-like and branched structures) using density functional-based tight-binding calculations and developed an interpolation scheme to reproduce the spectral features by encoding the structures using appropriate descriptors and selecting them through principal component analysis and Gaussian regression.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been used to simulate the properties of silicon with accuracy comparable to DFT, and efficiency comparable to empirical potentials. For example, Cao et al [15,27] learned the PES of Au 20 clusters by training an artificial neural network (ANN) potential to DFT data, which can give out binding energy within DFT accuracy. Ouyang et al have found a new Au 58 cluster by the combination of neural network potential and basinhopping method [28].…”
Section: Introductionmentioning
confidence: 99%